Some Common Fixed Points of Six Mappings on G_b-metric Spaces Using (E.A) Property (European Journal of Pure and Applied Mathematics, 2018)
The aim of this manuscript is to present a unique common fixed point theorem for six mappings satisfying $(φ ,ψ )$-contractions using (E.A) property in the framework of $G_{b}$- metric spaces. An illustrative example is also given to justify the established result.
Keywords: Complete $G_b$-metric space; Cauchy sequence; $(φ; ψ)$ contraction; (E.A) property; common fixed point; altering distance function; weakly compatible.